2022
DOI: 10.3847/1538-4357/ac80c0
|View full text |Cite
|
Sign up to set email alerts
|

Electron-scale Magnetic Peaks Upstream of Mercury’s Bow Shock: MESSENGER Observations

Abstract: Electron-scale magnetic peaks (ESMPs) with spatial sizes less than one local ion gyroradius have been recently revealed to exist in the terrestrial magnetosheath and solar wind at 1 au. Whether they widely exist in the astrophysical plasma is unclear. Here, we investigate the magnetic peaks with a period of 0.1–100 s upstream of Mercury’s bow shock by using the magnetic field data from the MESSENGER spacecraft. Based on the distribution of their durations, these magnetic peaks can be divided into two groups: o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The earliest observations of MHs date back to the work of Turner et al (1977), where these structures were identified for the first time in the solar wind (SW). Since then, satellite measurements have revealed that MHs are abundant not only in the SW (Winterhalter et al 1995(Winterhalter et al , 2000Chisham et al 2000;Russell et al 2008;Zhang et al 2008;Wang et al 2020a;Xiao et al 2014;Wang et al 2021b,c), but also in the Earth's magnetotail (Ge et al 2011;Sun et al 2012;Balikhin et al 2012;Huang et al 2019;Shustov et al 2019;Liu et al 2021), planetary magnetosheaths (Johnson & Cheng 1997;Soucek et al 2008;Volwerk et al 2008;Yao et al 2017;Huang et al 2017a;Zhong et al 2019;Yao et al 2020;Karlsson et al 2021;Huang et al 2021;Goodrich et al 2021), planetary bow shocks (Cattaneo et al 1998;Wang et al 2021a;Chen et al 2022;Huang et al 2022) and around comets (Russell et al 1987;Volwerk et al 2008). Magnetic holes come in many different sizes, covering a very broad range of scales.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest observations of MHs date back to the work of Turner et al (1977), where these structures were identified for the first time in the solar wind (SW). Since then, satellite measurements have revealed that MHs are abundant not only in the SW (Winterhalter et al 1995(Winterhalter et al , 2000Chisham et al 2000;Russell et al 2008;Zhang et al 2008;Wang et al 2020a;Xiao et al 2014;Wang et al 2021b,c), but also in the Earth's magnetotail (Ge et al 2011;Sun et al 2012;Balikhin et al 2012;Huang et al 2019;Shustov et al 2019;Liu et al 2021), planetary magnetosheaths (Johnson & Cheng 1997;Soucek et al 2008;Volwerk et al 2008;Yao et al 2017;Huang et al 2017a;Zhong et al 2019;Yao et al 2020;Karlsson et al 2021;Huang et al 2021;Goodrich et al 2021), planetary bow shocks (Cattaneo et al 1998;Wang et al 2021a;Chen et al 2022;Huang et al 2022) and around comets (Russell et al 1987;Volwerk et al 2008). Magnetic holes come in many different sizes, covering a very broad range of scales.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest observations of MHs date back to the work of Turner et al (1977), where these structures were identified for the first time in the solar wind (SW). Since then, satellite measurements have revealed that MHs are abundant not only in the SW (Winterhalter et al 1995;Chisham et al 2000;Winterhalter et al 2000;Russell et al 2008;Zhang et al 2008;Xiao et al 2014;Wang et al 2020aWang et al , 2021bWang et al , 2021c but also in the Earth's magnetotail (Ge et al 2011;Balikhin et al 2012;Sun et al 2012;Huang et al 2019;Shustov et al 2019;Liu et al 2021;Wang et al 2022), in planetary magnetosheaths (Johnson & Cheng 1997;Soucek et al 2008;Volwerk et al 2008;Huang et al 2017a;Yao et al 2017;Zhong et al 2019;Yao et al 2020;Goodrich et al 2021;Huang et al 2021;Karlsson et al 2021;Wu et al 2021;Chen et al 2022b), in planetary bow shocks (Cattaneo et al 1998;Wang et al 2021a;Chen et al 2022a;Huang et al 2022), and around comets (Russell et al 1987;Volwerk et al 2008). MHs come in many different sizes, covering a very broad range of scales.…”
Section: Introductionmentioning
confidence: 99%